Utilization Of Website-Based Technology For Analysis And Prevention Of Stunting Using The Fuzzy Tsukamoto Methods - Wijaya, Chandra; Asido, Elpri; Laia, Yonata; aisyah, siti; Radhi, Muhammad; amalia, Amalia; Fahmi, Mohammad Irfan Fahmi (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Stunting is a chronic malnutrition condition that has significant impact on inhibiting the growth of a child both physically and intellectually. The study aims toto analyze stunts using a web-based technology system using Tsukamoto’s Fuzzy method. This method was chosen for its ability to deal with the uncertainty and variability medical data. The system integrates various variables that affect stunts, such as nutritional intake and physical growth, to produce a more accurate diagnosis. The research was carried out by collecting data from various health sources and applying the fuzzy Tsukamoto method to process the data. The trial subjects in this developmental study were 30 children aged 1–60 months, or 0–5 years. Subjects were selected by random sampling, consisting of 6 children from 1–5 years of age each. Based on the results of the analysis, it appears that the fuzzy Tsukamoto-based system development trial can provide a better prediction of the risk of stunting in children compared to conventional methods. Using this approach, it is expected to help health workers take more accurate steps in the treatment and prevention of stunts. Keywords: Stunting, Fuzzy Tsukamoto Method, Nutritional Analyisis, Technology Systems, Child Heal